Dipti and Nina Ambani at Usha Kiran residence in Mumbai - Reliance Industries Limited (2023)
The Ambani family moved from the Alt View residency on Altamount road to the 22nd floor of Usha Kiran on Carmichael road during the 1970s. Ms. Dipti and Ms. Nina Ambani, daughters of Shri Dhirubhai Ambani, could be seen seated at their new residence in the photograph.